Exceptional responses to Trastuzumab deruxtecan in HER2-positive breast cancer: two illustrative case reports - Ballatore, Zelmira; Vanacker, Helene; Chiari, Rita; Bachelot, Thomas (Frontiers in Oncology, 2025)
BackgroundTrastuzumab deruxtecan (T-DXd), an antibody-drug conjugate targeting human epidermal growth factor receptor 2 (HER2), has demonstrated substantial clinical activity in metastatic HER2-positive breast cancer. Although durable responses are increasingly reported, the potential for long-lasting remission after treatment discontinuation remains poorly documented.CasesWe report two patients with metastatic HER2-positive breast cancer who experienced exceptional and sustained clinical benefit with T-DXd. The first patient achieved a deep response lasting over 50 months, including 36 months of complete remission after treatment discontinuation due to thrombocytopenia. The second patient has maintained disease control for over 39 months, with a prolonged treatment pause. Both cases highlight remarkable disease stability beyond conventional expectations.ConclusionThese case reports highlight the potential of T-DXd not only to induce deep and durable responses but also to maintain disease remission beyond drug exposure in selected patients. Such observations challenge the paradigm of incurability in metastatic HER2-positive breast cancer and warrant further investigation into the mechanisms and predictors of long-lasting responses.